Predominant Microbial Colonizers in the Root Endosphere and Rhizosphere of Turfgrass Systems: Pseudomonas veronii, Janthinobacterium lividum, and Pseudogymnoascus spp. - Xia, Qing; Rufty, Thomas; Shi, Wei (Frontiers in Microbiology, 2021)
Microbes can colonize plant roots to modulate plant health and environmental fitness. Thus, using microbes to improve plant adaptation to biotic and abiotic stresses will be promising to abate the heavy reliance of management systems on synthetic chemicals and limited resource. This is particularly important for turfgrass systems because intensive management for plant available nutrients (e.g., nitrogen), water, and pest control is necessary to maintain a healthy and aesthetic landscape. However, little is known on microbial species and host compatibility in turfgrass root endosphere and rhizosphere. Here, by using marker gene high throughput sequencing approaches we demonstrated that a few bacterial and fungal species prevailed the root endosphere and rhizosphere and were of a broad host spectrum. Irrespective of turfgrass species (bermudagrass, ultradwarf bermudagrass, creeping bentgrass, and tall fescue), defoliation intensities (i.e., mowing height and frequency), turfgrass sites and sampling time, Pseudomonas veronii was predominant in the root endosphere, constituting ~ 38% of the total bacterial community, which was much higher than its presence in the bulk soil (~ 0.5%) and rhizosphere (~ 4.6 %). By contrast, Janthinobacterium lividum and fungal species of the genus Pseudogymnoascus were more abundant in the rhizosphere, constituting ~ 15% and ~ 39% of the total bacterial and fungal community, respectively, compared to their respective presence in the bulk soil (~ 0.1% and 5%) and root endosphere (~ 0.8 % and 0.3%). Such stark contrasts in the microbiome composition between the root endosphere, rhizosphere, and bulk soil were little influenced by turfgrass species, suggesting the broad turfgrass host compatibility of these bacterial and fungal species. Further, their dominance in respective niches were mutually unaffected, implying the possibility of developing a multiple species formula for coping turfgrass with environmental stresses. These species were likely involved in controlling pests, such as infectious nematodes and fungi, decomposing root debris, and helping turfgrass water and nutrient uptake; yet these possibilities need to be further examined.